KAJIAN TERHADAP PERBEDAAN TINGKAT PENGUNGKAPAN LAPORAN KEUANGAN SEBELUM DAN SESUDAH SURAT EDARAN BAPEPAM N0. 02 TAHUN 2002 PERUSAHAAN PUBLIK DI INDONESIA - Abdul Rohman (Program Magister Akuntansi Unsyiah, 2008)
This research are computed the indexes reveal financial report among industries. In addition, giving an suggestion policy to agency which made policy about completing certainty of public firms who reveal financial report in Indonesia. This research pointed on practice of revealing financial report on public firm in Indonesia before prevail the realization about that policy by BAPEPAM on 2002. the method are items identification financial report and arrange indexes reveal financial report between industry for all thirteen industries. The second, identification toward the practice of revealing financial report after turn out the BAPEPAM policy on 2002. The indexes of revealing financial report between industry arrange and then considerate with the research result about the period before BAPEPAM policy turn out to see are there any significant differentiation. Based on the result of t-test showed that are significant different indexes reveal financial report the period before BAPEPAM policy turn with after turn out the BAPEPAM policy on 2002. Keyword Financial Performance, Ligimiality, Capital Structure and Profitability